2017
DOI: 10.1063/1.4999291
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric properties of lightly doped La:HfO2 thin films grown by plasma-assisted atomic layer deposition

Abstract: The structural and ferroelectric properties of lightly La-doped (1 mol. %) HfO2 thin films grown by plasma-assisted atomic layer deposition were examined. An annealing temperature as low as 400 °C crystallized the film into the desired orthorhombic phase, which resulted in it displaying promising ferroelectric performance. The remanent polarization (Pr) increased with annealing temperature, but the performance enhancement seemed to saturate at 500 °C. A slight decrease in the dielectric constant, which was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
37
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 33 publications
4
37
1
Order By: Relevance
“…However, the occurrence of a hysteresis in the plots of polarization P versus electric field E (Figure b) is well‐linked with the transition in the GIXRD patterns—similar to what has been shown in the literature . A maximum P r of 7 μC cm − 2 is observed for a concentration of 5 cat% of La that agrees with the La content used by Starschich and Boettger, and Yoneda et al In contrast, the optimum reported dopant contents for ALD films exhibit a strong variation with values ranging from 2 cat% (or even below) to around 10 cat% . Figure c shows the trends of remanent polarization P r and relative permittivity ε r with La content.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…However, the occurrence of a hysteresis in the plots of polarization P versus electric field E (Figure b) is well‐linked with the transition in the GIXRD patterns—similar to what has been shown in the literature . A maximum P r of 7 μC cm − 2 is observed for a concentration of 5 cat% of La that agrees with the La content used by Starschich and Boettger, and Yoneda et al In contrast, the optimum reported dopant contents for ALD films exhibit a strong variation with values ranging from 2 cat% (or even below) to around 10 cat% . Figure c shows the trends of remanent polarization P r and relative permittivity ε r with La content.…”
supporting
confidence: 84%
“…The order of magnitude of the effective d 33 as well as the observation of the decrease in displacement is in agreement with the earlier results ranging from 1 to 10 pm V −1 (Starschich et al quantified 10 pm V −1 for a unipolar measurement, whereas their Figure 2 suggests 20 pm V −1 for the pristine and 5 pm V −1 for the fatigued case of a bipolar large‐signal measurement). Nonetheless, this behavior requires further studies, and CSD films do not endure as many switching cycles as their ALD or PVD counterparts (10 5 –10 11 depending on the frequency and field used). Section S4, Supporting Information shows the behavior for the 45 nm‐thick film with the most prominent ferroelectricity (5 cat% La).…”
mentioning
confidence: 99%
“…In general, various resistance states are possible in a ferroelectric memristor because of the different degrees of inversion of the ferroelectric domains in the HZO film [23]. According to the PFM data, the polarization direction of the local HZO thin film domain is downward, that is, uniformly directed to p + -Si [42]. When a driving voltage is applied, the memristor's ferroelectric domain begins to flip.…”
Section: Science China Materialsmentioning
confidence: 99%
“…Since the initial report of near‐rectangular hysteresis with a high remanent polarization ( P r ) of 40 µC cm –2 was published for La:HfO 2 at 2013's International Electron Device Meeting (IEDM), researchers have tried to reproduce and explain this extraordinary result . A physical explanation for these results has remained elusive.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7] A physical explanation for these results has remained elusive. [2][3][4][5][6][7] A physical explanation for these results has remained elusive.…”
mentioning
confidence: 99%